Exciton-polariton laser diodes - Amthor, M. (2018)
Despite their name polariton lasers do not rely on stimulated emission of cavity photons. The less stringent threshold conditions are the cause that bosonic polariton lasers can outperform standard lasers in terms of their threshold currents. The part-light and part-matter quasiparticles called polaritons, can undergo a condensation process into a common energy state. The radiated light from such a system shares many similarities with the light emitted from a conventional photon laser, even though the decay of the polaritons out of the finite lifetime cavity is a spontaneous process. We discuss properties of polariton condensates in GaAs based microcavities. The system’s response to an external magnetic field is used as a reliable tool to distinguish between polariton laser and conventional photon laser. In particular, we will discuss the realization of an electrically pumped polariton laser, which manifests a major step towards the exploitation of polaritonic devices in the real world.